(untitled) (Research, Society and Development, 2022)
The lack of efficient management of public spending on health affects citizens primarily in their performance, in education and work, and in human development. Moreover, there is a global concern about public spending, especially in health, due to the scarcity of resources in the public sphere. Therefore, the objective of this study was to analyze the efficiency of Paraná municipalities in the management of public spending on health and sanitation and the variation of the HDI-M longevity factor, seeking to identify intervening variables in the period 2000-2009. For this, Data Envelopment Analysis (DEA) and Multiple Linear Regression were used. The results indicated five efficient municipalities and the intervening factors identified as intervening in the efficiency were: distance from the state capital; the number of occurrences of neoplasms in the population; the municipality being the headquarters of a health regional office, and the variation of the HDI-M Education factor. The contribution of the study lies in the identification of factors that intervene in the management of public spending in health, since the treatment of these factors can increase the longevity of the population. And yet, it was identified that increasing public spending on health and sanitation is not necessary, in some of the municipalities.